Perancangan dan Penerapan Sistem Pendukung Keputusan Pemilihan Supplier Terbaik Menggunakan Metode Analytical Hierarchy Process - Mujahid, Al Fattah Ibnu; Herlinda, Herlinda; Vandini, Intan (Journal Global Technology Computer, 2025)
This study aims to develop a decision support system for the supplier selection process using the Analytical Hierarchy Process method. The main problem addressed in this research is that the supplier selection process has been subjective and lacks transparency, which may affect the quality of procurement. The Analytical Hierarchy Process is applied to evaluate supplier alternatives based on several criteria, including price, quality, availability, and reputation. Each criterion is assigned a priority weight through pairwise comparisons, and the total scores are calculated to determine supplier rankings. The results of this study indicate that the method is effective in assisting decision-making in a more objective and structured manner. The main contribution of this research is the development of a decision support system that improves the efficiency and accuracy of supplier selection and supports optimal supply chain management.